Tests of Rational Expectations and Fisher Effects. - Lahiri, Kajal; Jungsoo Lee (Southern Economic Journal)
The main purpose of the present paper is to test the rational expectations hypothesis and the Fisher effect as two disjoint propositions. In addition, to highlight the implications of different expectational proxies on the estimated Fisher effect, we have used the well-known Livingston's series on price expectations which has recently been adjusted by Carlson [2]. Using the original Livingston's data, Cargill [1] has recently reported estimates of the Fisher effect in the treasury bill rates of different maturities. We, however, used the survey data in an errors-in-the variables framework and let the model decide the significance of the hypothesized sampling errors. Moreover, the use of Livingston's data in interest rate equations of different maturities typically produces the price expectations coefficients which are significantly more than one. Hendershott and van Home [11] have recently produced some evidence which shows that Livingston's data considerably underestimated the true price expectations implied by their interest rate equations. Thus, a systematic underestimation of true price expectations may very well explain the apparent overadjustment. We have tested the proposition by generalizing our econometric framework in which the survey measure and the REH were utilized as general indicators, rather than proxies for the unobservable price expectations variable. In this paper, we presented some additional econometric evidence on the "efficiency" of the six-month treasury bill market. To highlight the contrasting estimates that one obtains by utilizing different proxy measures for the unobservable price expectations, we have used the rational expectations framework and the Livingston's series to estimate the Fisher coefficient. The models fall neatly into Goldberger's unobservable-variable framework which im- plies certain non-linear constraints on the parameters across the reduced form equations. The main conclusions can be summarized as follows:.